Animals, evolution language: aspects of Whitehead in Italo Calvino’s Palomar - Fitzgerald, Brian (Spunti e Ricerche, 2016)
Despite contemporary scepticism of grand theory, Calvino’s Palomar is concerned with a unity of experience and the possibility of knowledge. But Mr Palomar’s quest for unity follows a process of failure. This begs the question of the novel’s fictivity, which creates a division of meaning between the immediate prose surface and the work as a whole whereby the novel does not provide certain answers to its own questions, only provisional ones. The reading that follows claims that Calvino is optimistic about both knowledge and unity, but that he declares this guardedly.